In Vitro Digestibility Evaluation of Fermented Coconut Meal Using Aspergillus Niger NRRL 337 - T. Purwadaria; T. Haryati; J. Darma; O. I. Munazat (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy